2018
DOI: 10.1126/sciadv.aao0167
|View full text |Cite
|
Sign up to set email alerts
|

Hallmarks of science missing from North American wildlife management

Abstract: Fundamental components of science are often lacking in U.S. state and Canadian provincial hunt management systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 31 publications
5
79
1
Order By: Relevance
“…Public agencies are under heightened scrutiny to deliver more rigorous assessments of environmental change and the status of natural resources (Reed 2008;Artelle et al 2018). Whether relating to field data collection, the identification of indicator species, or determining the likelihood of project-related impacts, EA must be underpinned by rigorously evaluating, testing, and ultimately drawing conclusions from the best available evidence (Treweek 1996).…”
Section: Component 3-scientific Rigourmentioning
confidence: 99%
“…Public agencies are under heightened scrutiny to deliver more rigorous assessments of environmental change and the status of natural resources (Reed 2008;Artelle et al 2018). Whether relating to field data collection, the identification of indicator species, or determining the likelihood of project-related impacts, EA must be underpinned by rigorously evaluating, testing, and ultimately drawing conclusions from the best available evidence (Treweek 1996).…”
Section: Component 3-scientific Rigourmentioning
confidence: 99%
“…Nevertheless, one recent evaluation of hunt management in the United States and Canada found little adherence to science-based approaches [12]. Using the criteria of Artelle et al [12], our assessment of available state management plans for pumas, indicates this to be the case for pumas in most of the western states. Additionally, there have been more recent calls for using science to evaluate the possible politicization of wildlife management decisions [13].…”
Section: Introductionmentioning
confidence: 88%
“…The NAM explicitly advocates the use of science and research in setting and justifying wildlife management policy [8,9,10,11]. Nevertheless, one recent evaluation of hunt management in the United States and Canada found little adherence to science-based approaches [12]. Using the criteria of Artelle et al [12], our assessment of available state management plans for pumas, indicates this to be the case for pumas in most of the western states.…”
Section: Introductionmentioning
confidence: 99%
“…We do not dispute the suitability of the solutions described by these authors, who provided examples of conservation and wildlife management interventions where they have usefully been employed, but we do question the extent of their utility. Artelle et al () found that the hallmarks of quality science were absent from the majority of 667 wildlife management approaches adopted in North America. This is likely to be due to the complexity of biological systems and the way in which scientists describe them, resulting in decision makers avoiding the use of robust scientific approaches for decision‐making (Addison et al , Hammersley ).…”
Section: Uncertainty In Decision‐makingmentioning
confidence: 99%